2020
DOI: 10.3389/fmicb.2020.01123
|View full text |Cite
|
Sign up to set email alerts
|

A Single Amino Acid Substitution in the Matrix Protein (M51R) of Vesicular Stomatitis New Jersey Virus Impairs Replication in Cultured Porcine Macrophages and Results in Significant Attenuation in Pigs

Abstract: In this study, we explore the virulence of vesicular stomatitis New Jersey virus (VSNJV) in pigs and its potential relationship with the virus's ability to modulate innate responses. For this purpose, we developed a mutant of the highly virulent strain NJ0612NME6, containing a single amino acid substitution in the matrix protein (M51R). The M51R mutant of NJ0612NME6 was unable to suppress the transcription of genes associated with the innate immune response both in primary fetal porcine kidney cells and porcin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 60 publications
1
26
0
Order By: Relevance
“…The molecular mechanisms of VSV pathogenesis remain unclear. Multiple studies suggest that interaction with immune cells and regulation of the immune response play a role in determining the outcome of infection [ 10 , 11 , 12 , 13 , 14 , 15 ]. Because of the important roles of immune cytokines in the pathogenesis of viral infection [ 29 ] and macrophages in the production of proinflammatory cytokines and their wide tissue distribution [ 28 ], VSV-infected porcine macrophages are an excellent model to extrapolate the molecular mechanisms of VSV pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The molecular mechanisms of VSV pathogenesis remain unclear. Multiple studies suggest that interaction with immune cells and regulation of the immune response play a role in determining the outcome of infection [ 10 , 11 , 12 , 13 , 14 , 15 ]. Because of the important roles of immune cytokines in the pathogenesis of viral infection [ 29 ] and macrophages in the production of proinflammatory cytokines and their wide tissue distribution [ 28 ], VSV-infected porcine macrophages are an excellent model to extrapolate the molecular mechanisms of VSV pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Infection with wild-type VSV induced weaker proinflammatory cytokine responses and downregulated the expression of the costimulatory molecule complex CD80/86 and MHC class II compared to the matrix protein mutant virus [ 11 ]. A matrix protein (M51R) VSV mutant virus replicated ~1000 times less in cultured primary porcine macrophages than its wild-type counterpart and showed significantly diminished virulence in pigs [ 13 ]. The molecular pathogenesis and immune evasion in natural hosts such as pigs and cattle have yet to be investigated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Infection with wildtype VSV induced weaker proinflammatory cytokine responses and downregulated the expression of the costimulatory molecule complex CD80/86 and MHC class II compared to the matrix protein mutant virus (11). A matrix protein (M51R) VSV mutant virus replicated ~1000 times less in cultured primary porcine macrophages than its wildtype counterpart and showed significantly diminished virulence in pigs (13). The molecular pathogenesis and immune evasion in natural hosts such as pigs and cattle have yet to be investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Macrophages play an important role in host defense against pathogens via positioning in all tissues where they can effectively sense danger signals with highly expressedPAMP receptors and producing a large quantity of both pro-and anti-inflammatory cytokines such as IL-1, IL-10, TGFβ and TNF via cell polarization and differentiation to regulate the immune response (28). Our previous study showed that primary porcine macrophages expressed higher levels of IFNβ and cytokines than primary fetal porcine kidney cell cultures after VSV infection (13). Given that VSV can infect and replicate in macrophages and the important role of macrophages in the immune response, ex vivo porcine macrophages were used as model cells to extrapolate the molecular mechanisms of VSV pathogenesis and immune evasion.…”
Section: Introductionmentioning
confidence: 99%